System on chip thermal vacuum sensor based on standard CMOS process - 李金凤 唐祯安 汪家奇 (Journal of semiconductors, 2009)
An on-chip microelectromechanical system was fabricated in a 0.5μm standard CMOS process for gas pressure detection. The sensor was based on a micro-hotplate （MHP） and had been integrated with a rail to rail operational amplifier and an 8-bit successive approximation register （SAR） A/D converter. A tungsten resistor was manufactured on the MHP as the sensing element, and the sacrificial layer of the sensor was made from polysilicon and etched by surface-micromachining technology. The operational amplifier was configured to make the sensor operate in constant current mode. A digital bit stream was provided as the system output. The measurement results demonstrate that the gas pressure sensitive range of the vacuum sensor extends from 1 to 105 Pa. In the gas pressure range from 1 to 100 Pa, the sensitivity of the sensor is 0.23 mV/Pa, the linearity is 4.95%, and the hysteresis is 8.69%. The operational amplifier can drive 200 Ω resistors distortionlessly, and the SAR A/D converter achieves a resolution of 7.4 bit with 100 kHz sample rate. The performance of the operational amplifier and the SAR A/D converter meets the requirements of the sensor system.